SIRT3 enhances the protective effect of Xyloketal B on seizure‐induced brain injury by regulating AMPK/mTOR signaling‐mediated autophagy - Fen‐Fang Chen; Jian‐Feng Liu; Di‐Mi Zhou (Kaohsiung Journal of Medical Sciences, 2024)
Abstract Brain damage in children due to seizures is irreversible and has been a major public health concern. The herbal monomer Xyloketal B (Xyl‐B) can be used as a neuroprotective drug because of its antioxidant, antiapoptotic, and anti‐inflammatory effects but with few adverse effects. In this article, we constructed a rat developmental convulsion model and a primary hippocampal neuronal cell convulsion model, through which we studied hippocampal neuronal morphology and neuronal apoptosis using H&E staining and TUNEL staining, respectively. Moreover, we measured TNF‐α, IL‐6, and IL‐1β inflammatory factor levels using ELISA, MDA, and SOD kits. The expression of SIRT3 in hippocampal tissues was determined by qPCR and Western blotting. The expression of autophagy‐related proteins such as LC3, p62, and Beclin‐1 was evaluated by Western blotting or immunohistochemistry. The role of SIRT3 and autophagic activity with Xyl‐B in convulsive seizure‐induced brain injury was investigated by knocking down SIRT3 expression levels. Our results showed that Xyl‐B plays a neuroprotective role in convulsive seizure‐induced brain injury by increasing SIRT3 expression and activating the autophagy pathway. The regulatory role of SIRT3 in the autophagy pathway with Xyl‐B treatment was explored by knocking down SIRT3 expression and inhibiting autophagy. Our results revealed that SIRT3 enhances the protective effect of Xyl‐B against postconvulsive brain injury by regulating AMPK/mTOR signaling‐mediated autophagy.